Improving Grade 9 mathematics learner achievement in an unsafe school environment in Gauteng, South Africa - Graham, Marien Alet (University of Pretoria, 2022)
Thesis (PhD (Assessment and Quality Assurance in Education and Training))--University of Pretoria, 2021.